Sugar Cane Mold Marketing Partnership By Sugar Cane Farmers In Mojokerto Regency - Oscarius Yudhi Ari Wijaya; Diah Rani Nartasari; Sulistiyani Sulistiyani (International Journal of Economics Development Research (IJEDR), 2023)
This study analyzes the sugarcane agribusiness partnership between the Gempolkrep Sugar Factory and sugarcane farmers, focusing on the partnership’s contribution to income, profits, and challenges faced. In a competitive business environment, marketing management plays a key role, with strategies like attractive packaging helping to draw customers. The research, conducted through in-depth interviews with 30 farmers using simple random sampling, applied qualitative and quantitative analysis. The partnership offers market guarantees, capital support, profit-sharing, and training while encouraging cooperation and limiting chemical use. Entrepreneurial groups also receive training in marketing, packaging, online presence, and accounting to boost production and expand market reach. Expected outcomes include the availability of larger storage tanks for molasses and sugarcane through government subsidies, increased income from higher sales, and enhanced business visibility and efficiency through blogs and online platforms.